САЛАМАТ ОЙЛАЎ-САЛАМАТ ДҮНЬЯТАНЫЎ - Абдимуратова, Н.П. (FAN va JAMIYAT, 2020)
The article deals with analysis of human cognition in different context the process of self-control, self-consionsness direct on upbringing of human being, moreover human is studied as an external, aesthetic and social factor of values.